Transfer function-based generalization of grid forming power synchronization loops - Ander Ordono; Javier Rodriguez-Gongora; Alain Sanchez-Ruiz; Markel Zubiaga; Francisco Javier Asensio; Jose Antonio Cortajarena (International Journal of Electrical Power & Energy Systems)
With the increasing penetration of inverter-based resources, grid forming control is expected to play a key role in stabilizing future grids. In these controllers, the power synchronization loop is in charge of synchronizing the inverter to the grid using an active power balance, removing the need for a phase-locked loop. Moreover, power synchronization loops can provide different services to the grid, including primary frequency regulation, inertial response or damping, among others. The aim of this work is to provide a generalization of power synchronization loops, classifying the existing strategies into six structures. Using their small-signal models, an analytical study is carried out, showing equivalences between controllers and identifying their main characteristics, limitations and tuning methodologies in grid-connected mode. The performance of different structures is also compared, evaluating their power setpoint tracking capability, the response against frequency excursions and the capability to filter phase jumps. Finally, analytical results are validated in an experimental testbench.